Measuring safety index for pedestrian path by using AHP-GIS / Athirah Illaina Mohammad Azlan and Nabilah Naharudin. - Mohammad Azlan, Athirah Illaina; Naharudin, Nabilah (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
Pedestrian crashes account for approximately 7 percent of road death in Malaysia. Although the percentage is lower than other road crashes, this is still alarming. This is because, no matter what vehicles used by people, they still need to walk. This includes riding rail transit services as people need to walk to access the service and walk again to their destination after getting off the rail service. Rail services’ providers and government had been committed to provide a safe walking environment to the transit riders. Therefore, this study attempted to propose a framework to measure the safety index by using AHP-GIS. The integration of the two techniques had been widely implemented in decision making related to spatial problems. In any spatial problems, there is always more than one criterion that needs to be taken into consideration in the analysis with each of them have different degree of importance in the analysis. Thus, the role of AHP in this framework is to derive the weightage for the criteria while GIS will use the weightage in the spatial analysis. In this proposed framework, GIS analysis that will be used in analysing the pedestrian safety is the assessment based on the parameters located along the road together. In short, this framework will first indicate the degree of importance of the criteria influencing safety by using AHP which will then be used to determine the safety index for pedestrian path using GIS. The proposed framework is expected to help in deriving the safety index for pedestrian path to access selected rail transit stations which can be used as a reference by pedestrian to choose the safe route that they can used to reach their destination. It also can be used by the local authority for improving the walking environment in future.